The Role of Banjarmasin Post Online Media in Educating Waste Management in North Banjarmasin - Hayatun Nupus; Muhammad Ainani (Universitas Lambung Mangkurat, 2026)
This study examines how Banjarmasin Post, a local online news outlet in South Kalimantan, frames waste management as a topic of public education in North Banjarmasin. Using Robert N. Entman's framing analysis model, this research analyzes three news articles published by the outlet in April 2025. The study uses a descriptive qualitative approach focused entirely on textual analysis, systematically applying Entman's four framing elements—problem definition, causal diagnosis, moral judgment, and treatment recommendation—to each article. The findings show that all three articles assign moral value to waste management efforts and include treatment recommendations consistent with public education goals. However, the framing consistently portrays the government and schools as the primary drivers of change, while overlooking structural barriers such as inadequate infrastructure and weak policy enforcement. The coverage of SDN Pengambangan 5 exhibits a characteristic individual responsibility frame, which places the burden of environmental change on individuals and educational institutions rather than on systemic actors. Overall, Banjarmasin Post's reporting remains event-driven and lacks the critical depth needed to sustain meaningful public education on waste management. These findings have implications for how local media can strengthen its role as an environmental communication platform.